Otorhinolaryngology in the COVID‐19 era: Are there significant differences between hospital‐based and private practices?. Issue 5 (10th February 2021) - Guha, Anasuya; Plzak, Jan; Schalek, Petr; Chovanec, Martin
Abstract: Objectives: The COVID‐19 disease has an incredible impact on both hospital‐based and private practices in the field of otorhinolaryngology and head and neck surgery. Practical issues faced by both types of practices have not been well addressed in most studies. A national survey was conducted in April 2020 to identify the challenges faced by otorhinolaryngologists practicing in the Czech Republic. Design: Prospective questionnaire‐based study Setting: Online Google questionnaire sent to the members of the Czech Society of Otorhinolaryngology and Head and Neck Surgery Participants: All doctors practicing Otorhinolaryngology in the Czech Republic with access to the online questionnaire between 15th and 26th April 2020. Main outcome measures: The primary aims of the study were to evaluate any significant differences between the two types of practice in the field of Otorhinolaryngology. We formulated null hypotheses stating there were no statistical differences in the preparation and availability of personal protective equipment amongst both practices a month after the first case of COVID‐19 in the Czech Republic. Statistical analyses including the Mann‐Whitney U test were performed to test the hypotheses. Results: Analysis and results were based on the completion of the entire questionnaire by the doctors. There were no statistically significant differences between both the practices; however, individual analyses of both the practices showed a different outcome. Conclusion: Despite our statistical results, it was observed that private practices faced more deficits and were more financially vulnerable. They were also other issues reported by both practices that could compromise the care of patients, functioning of workplaces and support of doctors.